A systematic approach to hospital school management (MMIT Proceedings, 2025)
This article explores the application of a systematic approach in the management of a hospital school, an educational organization operating in a medical environment. The theoretical and methodological basis is revealed, including the concepts of learning as a system, as well as procedural and infrastructural aspects. Foreign cases of the application of systems theory in educational and hospital institutions are presented. The emphasis is placed on the role of interacting subsystems — pedagogical, clinical, administrative — and feedback mechanisms to ensure the quality of education and the health of students